Reaper scripts for beginners - Lauritsen, David (Packt Publishing, 2025)
Reaper's scripting capabilities allow you to automate tasks, customize workflows, and unlock new creative possibilities. This beginner-friendly course introduces you to ReaScript using Lua, guiding you through setting up your environment, writing scripts, and understanding key programming concepts. You'll start with simple scripts and gradually build more advanced automation tools. As you progress, you'll explore essential coding techniques like functions, loops, and logic while applying them to real-world tasks. You'll create scripts to move items, adjust track properties, and insert FX, reinforcing your learning with hands-on exercises. Theory lessons and homework challenges ensure you develop practical skills while deepening your understanding of ReaScript. By the end of this course, you'll confidently write custom scripts, automate repetitive actions, and enhance Reaper's functionality to suit your workflow. Whether you're a producer, musician, or engineer, this course will give you the tools to streamline your projects and improve efficiency. To access the supplementary materials, scroll down to the 'Resources' section above the 'Course Outline' and click 'Supplemental Content.' This will either initiate a download or redirect you to GitHub. What you will learn Set up ReaScript and write basic Lua scripts in Reaper. Apply loops, functions, and logic to automate tasks. Manipulate items, tracks, and FX using custom scripts. Create scripts for workflow enhancements and automation. Develop advanced scripts for region management and FX control. Customize Reaper with personalized scripting solutions. Audience This course is for Reaper users looking to automate tasks and improve workflow, beginners with little to no coding experience, audio professionals wanting to customize Reaper with Lua scripting, and anyone interested in learning the fundamentals of ReaScript. About the Author David Lauritsen: David Lauritsen is a seasoned Audio Engineer and Sound Designer based in Melbourne, Australia. With professional expertise in music recording and mixing since 2014 and in film and television audio production, postproduction, and sound design since 2015, he brings a wealth of experience to every project. His diverse portfolio includes music LPs and EPs, feature films, video games, TV shows, live events, and podcasts. Previously, as Head Lecturer of the Audio Engineering undergraduate program at JMC Academy, David helped shape the next generation of audio professionals. He currently applies his creative vision as a full-time sound designer at a leading video game company in Melbourne.
Online resource; title from title details screen (O'Reilly, viewed March 17, 2025)
Keywords: Computer programming; Programmation (Informatique); computer programming; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet